POSITIVE SELF TALK AND COUNSELLING TO OVERCUM MATHEMATICS ANXIETY AMONG SECONDARY SCHOOL STUDENTS (Journal of Pharmaceutical Negative Results, 2022)
A solid foundation in mathematics and science develops and hones the skills of posing hypotheses, designing experiments and controls, analyzing data, recognizing patterns, seeking evidence, conclusions and proof, solving problems and seeking absolutes, while being open to new information.To raise math accomplishment levels, it is necessary to acknowledge the need for fresh approaches and methods. The goal of the study is to determine how well metacognitive interventions affect arithmetic achievement about gender and intellect. It is a natural experiment study. For the study, samples of 60 Xth standards were selected. Two groups, a control group, and an experimental group were created from the sample. Each group consists of 30 students in each group. The experimental group received instruction using math modules built on Positive self talk and psychological intervention, while the control group received instruction using conventional lesson plans. The study's findings demonstrated that Positive Self talk has a considerable impact on mathematical achievement. The learning of mathematics, as well as the teaching of mathematics, can both benefit from Psychological Counselling. Therefore, it can be inferred that employing metacognitive methods and procedures can improve secondary school students' mathematical achievement and sutantial decreament in Maths anxiety.